Case Report: A Case of Severe Clinical Deterioration in a Patient With Multiple Sclerosis - Breitkopf, Katharina; Aytulun, Aykut; Förster, Moritz; Kraus, Bastian; Turowski, Bernd; Huppert, Doreen; Goebels, Norbert; Hefter, Harald; Aktas, Orhan; Metz, Imke; Brück, Wolfgang; Reifenberger, Guido; et al. (Frontiers in Neurology, 2020)
Tumefactive multiple sclerosis is a rare variant of multiple sclerosis (MS) that may lead to a rapidly progressive clinical deterioration requiring a multidisciplinary diagnostic work up. Our report describes the diagnostic and therapeutic approach of a rare and extremely severe course of MS. A 51-year-old man with an 8-year history of relapsing-remitting multiple sclerosis (RRMS) was admitted with a subacute progressive left lower limb weakness and deterioration of walking ability. After extensive investigations including repeated MRI, microbiological, serological, CSF studies and finally brain biopsy the diagnosis of a tumefactive MS lesion was confirmed. Despite repeated IV steroids as well as plasma exchanges and IV foscarnet and ganciclovir due to low copy numbers of HHV-6 DNA in PCR analysis the patient did not recover. The clinical presentation of tumefactive MS is rare and variable. Brain biopsy for histopathological work-up should be considered in immunocompromised patients with rapidly progressive clinical deterioration with brain lesions of uncertain cause.